-3x+4=-6x+16

Simple and best practice solution for -3x+4=-6x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+4=-6x+16 equation:


Simplifying
-3x + 4 = -6x + 16

Reorder the terms:
4 + -3x = -6x + 16

Reorder the terms:
4 + -3x = 16 + -6x

Solving
4 + -3x = 16 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
4 + -3x + 6x = 16 + -6x + 6x

Combine like terms: -3x + 6x = 3x
4 + 3x = 16 + -6x + 6x

Combine like terms: -6x + 6x = 0
4 + 3x = 16 + 0
4 + 3x = 16

Add '-4' to each side of the equation.
4 + -4 + 3x = 16 + -4

Combine like terms: 4 + -4 = 0
0 + 3x = 16 + -4
3x = 16 + -4

Combine like terms: 16 + -4 = 12
3x = 12

Divide each side by '3'.
x = 4

Simplifying
x = 4

See similar equations:

| 60=a/1-.4 | | (5x-5)+(8x-48)=180 | | V=1/3*3.14*rx^2*h | | 2x+3y=4fory | | -5x^2+7x-10=0 | | [m+5]+9=16 | | X=4y-25 | | =4*3*3 | | 3/9=4/r-s | | 0.6v+2.1=17 | | X^3+px^2+px+1=0 | | (Y)(Y)=0 | | 6/9=n/3 | | 2x-6=9x+9 | | 2X-5y-3xy=0 | | 16x^2+70x-9=(Ax+B)(Cx-D) | | |4x-1/3|=1 | | 2x^2-16=20 | | 2X-0.5y-0.001xy=0 | | 502.4=3.14*4x^2*h | | 49w^2-25f^2= | | 2x+6=4x+20 | | .06x=1 | | (-1)-3-(-11)+(-9)= | | 5x-3(x-6)=3+3x | | -2xt^2-11=5 | | X^2+2x+2.5=0 | | 3+2x+11=6x+33 | | x-(.15x)=130 | | factorz^2+z-12= | | 21x^2y+3xy-35x-5=0 | | (X^4y^3)(xy^6)= |

Equations solver categories